1989
DOI: 10.1210/jcem-68-3-647
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pattern of Postprandial Carbohydrate Metabolism After Ingestion of a Glucose Drink or a Mixed Meal*

Abstract: To determine whether the postprandial pattern of carbohydrate metabolism differs after ingestion of an identical amount of glucose as either a drink or as a part of a mixed meal, normal subjects were studied on two occasions. On both occasions, hepatic and extrahepatic glucose metabolism were assessed using the dual isotope and forearm catheterization techniques as well as indirect calorimetry. Plasma glucose, insulin, and C-peptide concentrations and rate of systemic entry of ingested glucose all were lower (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…A primed (12 mg/kg) continuous (0.12 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 ) infusion of [6,6-2 H 2 ]glucose (MassTrace, Woburn, MA) started at 0700. At time 0, i.e., 1000, subjects ingested a standard mixed meal within 15 min, which consisted of three scrambled eggs, 55 g Canadian bacon (or 47 g steak), and Jell-O containing 75 g glucose that was enriched (to ϳ4%) with [1-13 C]glucose, as previously described (18,26). An intravenous infusion of [6-3 H]glucose was started at the same time and infused in a pattern that minimized the change in the ratio of plasma tracer (i.e., [6-3 H]glucose) to plasma meal tracee (i.e., [1-13 C]glucose).…”
Section: Methodsmentioning
confidence: 99%
“…A primed (12 mg/kg) continuous (0.12 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 ) infusion of [6,6-2 H 2 ]glucose (MassTrace, Woburn, MA) started at 0700. At time 0, i.e., 1000, subjects ingested a standard mixed meal within 15 min, which consisted of three scrambled eggs, 55 g Canadian bacon (or 47 g steak), and Jell-O containing 75 g glucose that was enriched (to ϳ4%) with [1-13 C]glucose, as previously described (18,26). An intravenous infusion of [6-3 H]glucose was started at the same time and infused in a pattern that minimized the change in the ratio of plasma tracer (i.e., [6-3 H]glucose) to plasma meal tracee (i.e., [1-13 C]glucose).…”
Section: Methodsmentioning
confidence: 99%
“…used in study A except that 50 Ci [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]glucose was added to allow determination of 14 C specific activity of urinary acetaminophen glucuronide and hence quantitation of the percent contribution of the direct and indirect pathways of glycogen synthesis (17). Urine samples were collected every 2 h for measurement of 14 C-acetaminophen-glucuronide specific activity, and frequent blood samples were taken for measurement of glucose, [ 14 C]glucose, and plasma insulin.…”
Section: Study Cmentioning
confidence: 99%
“…Considerable caution has to be exercised in extrapolating from such data as the time course of changes after eating is not reproduced and as available evidence suggests that the relative disposition of glucose in muscle and liver differs considerably after administration by the two routes (4)(5)(6). A few studies have followed the fate of a pure glucose load (7)(8)(9)(10), but the metabolic response to a glucose load differs from that after a mixed meal (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that although addition of protein and fat to a mixed meal results in a slight delay in meal appearance in comparison to ingestion to the same amount of glucose alone, the overall glycemic profile is virtually identical, with 2-h glucose concentrations in both instances being close to preprandial levels (39). Similarly, because ingestion of complex carbohydrates blunts the postprandial rate of rise of glucose, the concentrations at 2 h are closer to preprandial level than they are to the postprandial peak.…”
Section: Prediction Of Postprandial Glucose Area Above Basalmentioning
confidence: 99%